Determinants of Budget Deficit in Nigeria - Maimuna M Shehu; Ibrahim M Adamu (Journal of International Business, Economics and Entrepreneurship, 2021)
This paper investigates the factors governing the determination of budget deficit in Nigeria from 1981q1 through 2016q4. Our methodology is based on Johansen cointegration and Vector Error Correction model (VECM) approach. The result from the Johansen cointegration test suggests one cointegrating vector, which indicates the existence of a long run cointegrating relationship. Evidence from the long run and short run parameters suggest that exchange rate, interest rate and one year lag of budget deficit are the major determinants of budget deficit. Therefore, to achieve a realistic fiscal surplus, the government should determine a high level of accountability in its fiscal operations. In addition, any fiscal surplus should be channeled into productive investments to diversify the economy and reduce the likelihood of potential budget deficits.